Pengembangan Aplikasi ZIS Share untuk Menumbuhkan Kesadaran Membayar Zakat, Infaq dan Sedekah pada Siswa SD - Maula, Mela Minkhatul; Surya, Ade; Ramadhan, Alif Akbar Bayu; Aeni, Ani Nur (AS-SABIQUN, 2023)
This study explores the use of applications as interactive learning media in Islamic Education (PAI) learning about zakat, infaq, and alms for elementary school students. The research was carried out using the Design and Development (D&D) approach, through a series of studies on the design, development and evaluation processes using instruments in the form of field documentation, surveys and questionnaires. through a series of studies using the ADDIE model consisting of analysis, design, implementation development and evaluation using instruments in the form of field documentation, surveys, and questionnaires. The results of data processing are carried out qualitatively and quantitatively and are made into several themes. The results of the study show that the ZIS share application by displaying audiovisuals, podcasts and interactive quizzes in it is able to make learning more varied and interesting for students. The majority of students feel happy when using the ZIS share application. This research is formulated in three points as follows: (1) What is the design of the ZIS share application for PAI learning regarding awareness of paying zakat, infaq and alms in elementary school?, (2) What is the effectiveness of using the ZIS share application?, (3) The following are the results of this study: (1) Validity was tested by asking two material experts to provide an assessment of the application product in terms of design, audio quality, grammar, suitability of the material, and navigation. The results show that the average rating for suitability of material and design is 100%, while for navigation is 85%, which indicates a very valid category. (2) Practicality is tested by asking students to provide an assessment and response after using the media. The results show that the average percentage of ratings for design, navigation, and material suitability is 80% and 87%. In conclusion, the ZIS share application is an interactive learning media that is effective and useful in increasing students’ awareness of zakat, infaq, and alms and being able to make PAI learning more interesting for elementary school students.